2004
DOI: 10.1113/jphysiol.2004.061655
|View full text |Cite
|
Sign up to set email alerts
|

SUR2A C‐terminal fragments reduce KATP currents and ischaemic tolerance of rat cardiac myocytes

Abstract: C-terminal fragments of the sulphonylurea receptor SUR2A can alter the functional expression of cloned ATP-sensitive K + channels (K ATP ). To investigate the protective role of K ATP channels during metabolic stress we transfected SUR2A fragments into adult rat cardiac myocytes. A fragment comprising residues 1294-1358, the A-fragment, reduced sarcolemmal K ATP currents by over 85% after 2 days (pinacidil-activated current densities were: vector alone 7.04 ± 1.22; and A-fragment 0.94 ± 0.07 pA pF −1 , n = 6,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…It has been proposed that a PKC-induced increased trafficking of K ATP to the sarcolemma (Budas et al, 2004), which opens sarcolemmal K ATP causing shortening of myocyte action potential duration and reduced Ca 2ϩ influx (Rainbow et al, 2004), is responsible for preconditioninginduced protection (Gross, 1995). However, a number of observations are inconsistent with this conjecture, including the demonstration of protection independent of surface current changes in isolated nonbeating myocytes (Garlid et al, 1997;Liu et al, 1998b) and the ability of some K ATP openers to protect against ischemia/ reperfusion injury at doses or concentrations that do not influence the action potential duration (Yao and Gross, 1994;Grover et al, 1995Grover et al, , 1996.…”
Section: Figmentioning
confidence: 99%
“…It has been proposed that a PKC-induced increased trafficking of K ATP to the sarcolemma (Budas et al, 2004), which opens sarcolemmal K ATP causing shortening of myocyte action potential duration and reduced Ca 2ϩ influx (Rainbow et al, 2004), is responsible for preconditioninginduced protection (Gross, 1995). However, a number of observations are inconsistent with this conjecture, including the demonstration of protection independent of surface current changes in isolated nonbeating myocytes (Garlid et al, 1997;Liu et al, 1998b) and the ability of some K ATP openers to protect against ischemia/ reperfusion injury at doses or concentrations that do not influence the action potential duration (Yao and Gross, 1994;Grover et al, 1995Grover et al, , 1996.…”
Section: Figmentioning
confidence: 99%
“…Action potential and cell-attached patch recordings were made as previously described [19]. displaying a cardioprotected phenotype may be prepared using a "stop-start" perfusion protocol in a whole heart mounted on a Langendorff perfusion system prior to enzymatic isolation of cardiomyocytes [27].…”
Section: Patch-clamp Electrophysiologymentioning
confidence: 99%
“…Evidence for a key role for the cardiac K ATP channel comes from the observation that pharmacological blockade [12,18], disruption of channel expression with interacting fragments of SUR [19], shRNA knockdown [3] and knockout of Kir6.2 subunits [20,21] all have deleterious effects on the ability of IPC and other cardioprotective stimuli to impart protection.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the recent studies that involved the use of sarcK ATPspecific inhibitors and genetic models of disrupted or knocked-out sarcK ATP channel subunits indicated that the role of sarcK ATP channel in cardioprotection should not be ignored. (51,52) We have demonstrated that isoflurane can stimulate K ATP channels in isolated ventricular myocytes. (20,40,41,48,49,53,54) In addition, our laboratory has shown that the K ATP channel agonist pinacidil exerts greater effects to open the K ATP channel in myocytes that were previously subjected to isoflurane.…”
mentioning
confidence: 99%